Pressure-driven functional polymeric membrane technology as athermal separation unit operation in chemical engineering : A Review - Aspiyanto Aspiyanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2019)
This manuscript provides an overview of published scientific and trade literatures and a collection of useful reference information on all aspects of membrane science and technology, selected result of experiment applications, and more recent developments in pressure-driven flat sheet membrane (PDFSM) processes as new frontier and athermal separation unit operation in chemical engineering covering general description of the basic principles of membrane separation processes, benefits and drawbacks, and future trends of membrane developments. Meanwhile, experiment results of selected applications of membranes are removing and/or reducing bacteria, and recovering high protein and low fat from skim milk by microfiltration (MF) membrane as an alternative to replace heat sterilization, separating and/or concentrating protease enzyme by ultrafiltration (UF) membrane, separating target and valuable components in corn steeping water by using nanofiltration (NF) membrane, separating and/or purifiing ions component in brackish water and sea water by hyperfiltration (HF) or reverse osmosis (RO) membrane, and separating and/or concentrating desired and valuable components in guava fruit juice through hyperfiltration (HF) or reverse osmosis (RO) membrane.